Negotiations on the Global Goal on Adaptation (GGA): State of play and opportunities for farmers to engage - Njuguna, L. (2025)
This presentation provides an overview of international negotiations under the United Nations Framework Convention on Climate Change (UNFCCC) to operationalise the Global Goal on Adaptation (GGA) established under the Paris Agreement. It traces the evolution of the GGA from the Glasgow–Sharm el-Sheikh (GlaSS) work programme through the 27th Conference of the Parties’ (COP27’s) structured framework and the COP28 United Arab Emirates (UAE) Framework for Global Climate Resilience, which introduced the UAE–Belém Work Programme on GGA indicators. The presentation outlines current efforts to develop a manageable set of indicators. It gives an overview of the UAE Framework, highlighting the prioritised sectors: water, food and agriculture, health, ecosystems, infrastructure, cultural heritage and livelihoods. It provides a roadmap to COP30, highlighting critical milestones. It closes with identifying entry points for farmer organisations, such as the Eastern Africa Farmers Federation (EAFF), to engage in shaping adaptation indicators and ensuring that local realities and knowledge systems are reflected in the global adaptation framework.